Introduction to money laundering deterrence - Cox, Dennis W. (Chichester, Hoboken, N.J. : Wiley, 2010)
This book will look at a series of types of money laundering, explain how they are used and what controls, if any, could be used by an institution to protect itself. What should make a banker suspicious how would suspicion appear to a court or regulator, and what will the impact be on controls and reputational risk.
Includes index
oif 23/05/13
Loan
Keywords: Money laundering; Money laundering -- Prevention; Terrorism -- Finance; Terrorism -- Prevention